Ett upplevelseproduktionsperspektiv med värdskap i förgrund : En studie om värdskapsbegreppets relevans för bra arbetsmiljö - Persson, Therése (2012)
The experience industry and experience society has evolved and become increasingly important because the human majority now live a well economical life and therefore want to experience things beyond their everyday lives. An experience is largely composed of the treatment from other people on the spot, often from the people working there. The staffs become part of the overall experience. A study has been done to get a vision of what defines a good workplace and if a perspective of experience production with hospitality in the foreground has any relevance to it. In this study, I assumed from my own perspective I received during my years as a student at Experience Production at Luleå University of Technology. Hospitality has been at the forefront because for me it is a big part of the experience production since it deals with how to treat and look at the new people you meet.To get an idea of what defines a good place to work in theory, a literature study has been made. From this study, concepts selected who were frequent and that best described what is considered a good place to work. Although an empirical study has been made, the results have shown how an institution and various companies reason about what is a good place to work. Frequent concept has also been highlighted from the empirical study of the institute and businesses.The results in the literature and empirical study has generated in a model where the concepts gathered. A comparison showed the relevance of a perspective of experience production with the hospitality in the foreground, as the concepts of literature and empirical study was concordant with the perspective of experience production. The study also showed that the perspective of experience production had four more concepts to the model. Therefore was the conclusion a further model to show that perspective of experience production are relevant to a good workplace and have concepts for developing the work of what a great workplace entails. Validerat; 20120625 (anonymous)